The hunt for another Earth: a love story. (January 2021) - Gardner, Kate
Abstract : Massachusetts Institute of Technology (MIT) planetary scientist Sara Seager's memoir is a love story, where love comes in multiple forms: romantic love, parental love, friendship, plus love of nature, of the universe and of maths. The Smallest Lights in the Universe: a Memoir opens with Seager recounting a particularly bad day six months after the death of her husband.